The Effect of Top G2 Liquid Organic Fertilizer and SP-36 Fertilizer on Peanut Plant Growth and Yield: Pengaruh Pupuk Organik Cair TOP G2 dan Pupuk SP-36 Terhadap Pertumbuhan dan Produksi Tanaman Kacang Tanah - Robert Alberth Sole (Universitas Widya Gama Mahakam, 2021)
The purpose of this study is to find out the effect of the administration of Top G2 liquid organic fertilizer and SP-36 fertilizer on peanut crop yields, to know the dose of SP-36 fertilizer and Top G2 liquid organic fertilizer that can produce the best peanut crop results and to know the interaction of liquid organic fertilizer Top G2 and SP-36 fertilizer in improving the yield of peanut crops. The design used in this study is a Randomized Group Design (RGD) factorial pattern. This treatment consists of two factors: First Factor: Concentration of POC Top G2 consisting of OC0: No POC Top G2, OC1: POC Top G2 4 cc ltr air-1petak-1 OC2: POC Top G2 8 cc ltr water-1Swath-1; The second factor: Fertilizer Dose P (SP36) consists of P0: Without SP36 fertilizer; P1: 300 kg ha-1; Q2: 400 kg ha-1. The results showed that the administration of g2 top liquid organic fertilizer with a concentration of 8 cc ltr water-1 produced the highest plant height of 20.75 cm tan-1, the number of leaves 27.36 strands of tan-1, the number of pods 39.89 tan-1 and the harvest index 0.326. The interaction of g2 top liquid organic fertilizer and phosphorus fertilizer increases the weight of dried seeds harvesting crops, i.e. in the treatment of liquid fertilizer concentration top G2 8 cc ltr water-1 plot-1 with a seed weight of 235 g tan-1. Cultivation of peanut crops should use liquid organic fertilizer top G2 concentration eight cc tr water-1 tile-1 and need further research using higher concentrations of liquid organic fertilizer top G2 to see the optimum needs of peanut crops.